2011
DOI: 10.1124/dmd.110.036400
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of CYP3A-Mediated Drug-Drug Interactions Using Human Hepatocytes Suspended in Human Plasma

Abstract: ABSTRACT:Cryopreserved human hepatocytes suspended in human plasma (HHSHP) represent an integrated metabolic environment for predicting drug-drug interactions (DDIs). In this study, 13 CYP3A reversible and/or time-dependent inhibitors (TDIs) were incubated with HHSHP for 20 min over a range of concentrations after which midazolam 1-hydroxylation was used to measure CYP3A activity. This single incubation time method yielded IC 50 values for the 13 inhibitors. For each CYP3A inhibitor-victim drug pair, the IC 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 61 publications
3
50
0
Order By: Relevance
“…2008;Xu et al, 2009;Chen et al, 2011;Li and Doshi, 2011). We agree with Mao et al, and others who have also suspected that the use of microsomes tends to overestimate P450 enzyme inhibition, and that incorporating cell membrane permeability and phase II enzyme transformation with intact hepatocytes will provide a more reliable prediction of natural product interactions with P450 enzymes Mao et al, 2011). It might be ideal to combine inhibition and induction studies in a single assay by determining both P450 activities and expression changes simultaneously.…”
Section: Recommendations For Future Interaction Studiessupporting
confidence: 64%
“…2008;Xu et al, 2009;Chen et al, 2011;Li and Doshi, 2011). We agree with Mao et al, and others who have also suspected that the use of microsomes tends to overestimate P450 enzyme inhibition, and that incorporating cell membrane permeability and phase II enzyme transformation with intact hepatocytes will provide a more reliable prediction of natural product interactions with P450 enzymes Mao et al, 2011). It might be ideal to combine inhibition and induction studies in a single assay by determining both P450 activities and expression changes simultaneously.…”
Section: Recommendations For Future Interaction Studiessupporting
confidence: 64%
“…The ideal in vitro system for comprehensively evaluating drug-drug interactions should theoretically be human hepatocytes (Zhao, 2008), given the full complement of metabolic clearance mechanisms. Even though the ability to conduct in vitro DDI studies has been demonstrated in human hepatocyte suspensions (Mao et al, 2011), there are limitations with the long-term viability and enzymatic activity of the cells in suspension (Zhao, 2008). It has been demonstrated that human plated cell systems offer unique advantages over human cell suspensions for time-dependent inhibition studies (Li and Doshi, 2011).…”
Section: Albaugh Et Almentioning
confidence: 99%
“…Many investigators have evaluated the use of hepatocyte suspensions (Zhao et al, 2005(Zhao et al, , 2007McGinnity et al, 2006;Van et al, 2007;Lu et al, 2008a,b;Baer et al, 2009;Mao et al, 2011) for time-dependent inhibition studies. The use of hepatocytes for timedependent inhibition holds distinct advantages over the use of microsomes, including being more physiologically relevant and offering the ability to conduct longer incubations.…”
Section: Introductionmentioning
confidence: 99%
“…After cessation of administration with the TDI inhibitor, the patient would continue to have decreased drug metabolizing capacity before the inactivated enzymes are fully replaced 23,36 . While TDI is generally studied using liver microsomes or recombinant CYP 37,38 , there are substantial efforts in the evaluation of this important mechanism of drug-drug interaction in human hepatocytes 39,40 . Human hepatocytes, because of the intact plasma membrane, complete and uninterrupted drug metabolism enzymes and cofactors, represent a desirable in vitro experimental system for the evaluation of human drug properties.…”
Section: -Well Time-dependent Inhibition Assay For Cyp3a4 In Human mentioning
confidence: 99%
“…Traditionally, TDI studies with hepatocytes utilize suspension cultures 40 . The use of hepatocytes in suspension culture is a common practice with cryopreserved cells as most preparations of cryopreserved hepatocytes would have compromised ability to be cultured as monolayer cultures.…”
Section: -Well Time-dependent Inhibition Assay For Cyp3a4 In Human mentioning
confidence: 99%